2003
DOI: 10.3354/meps246115
|View full text |Cite
|
Sign up to set email alerts
|

Importance of benthic nutrient regeneration during initiation of macroalgal blooms in shallow bays

Abstract: Fast growing ephemeral algae are increasingly observed in shallow coastal waters worldwide. This is generally considered a symptom of coastal eutrophication. It has been suggested that the reoccurrence of macroalgal mats, despite ongoing efforts to decrease nutrient loadings, may be explained by the fact that sheltered bays function as self-regenerating systems through benthic regeneration of nutrients. The importance of benthic nutrient regeneration during the initiation of the growth of filamentous green alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 43 publications
2
47
0
1
Order By: Relevance
“…Growth during this phase might have been partially supported by stored N, since dissolved inorganic nitrogen in the water column was low during spring (Pedersen & Borum 1996). In addition, rapid uptake of inorganic nitrogen mineralised in the sediment has been shown to support the growth of macroalgal blooms (Sundbäck et al 2003).…”
Section: Biomass and Chemical Composition Of Macroalgaementioning
confidence: 99%
See 2 more Smart Citations
“…Growth during this phase might have been partially supported by stored N, since dissolved inorganic nitrogen in the water column was low during spring (Pedersen & Borum 1996). In addition, rapid uptake of inorganic nitrogen mineralised in the sediment has been shown to support the growth of macroalgal blooms (Sundbäck et al 2003).…”
Section: Biomass and Chemical Composition Of Macroalgaementioning
confidence: 99%
“…N, P) released from the sediment during the mineralisation of organic matter. It has been suggested that in this way the production of ephemeral green macroalgae could be self-regenerating (Lavery & McComb 1991, Sundbäck et al 2003.…”
Section: And N Contents Of the Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of increasing trends in N loads over recent decades have been attributed to elevated NO 3 -inputs to coastal waters (Cloern 2001, Howarth et al 2002, which are largely responsible for increases in the occurrence of macroalgal blooms (Sfriso et al 1992, Valiela et al 1992, Cloern 2001. NH 4 + inputs from raw sewage, aquaculture activities, and dissolved organic nitrogen from benthic nutrient regeneration are increasingly more common, and also support macroalgal production (Trimmer et al 2000, Tyler et al 2001, Sundback et al 2003, Barile 2004, Lapointe et al 2005a,b, Tsai et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Benthic nutrient fluxes (BNF) can supply a substantial proportion of the nutrient requirements of benthic and pelagic algae in an estuary (30 to 100%) and, thus, they potentially sustain the benthic and pelagic primary production within the estuarine food web (Kemp & Boynton 1992, Berelson et al 1998, Gibbs et al 2002, Sundbäck et al 2003. Generally, investigations of BNF concentrate on the role of microbial processes, associated with coupled nitrification -denitrification, and the microphytobenthos, which intercept the nutrient fluxes at the sediment -water interface (e.g.…”
Section: Introductionmentioning
confidence: 99%